SOSIALISASI DAN ASISTENSI VALIDASI NOMOR INDUK KEPENDUDUKAN (NIK) MENJADI NOMOR POKOK WAJIB PAJAK (NPWP) ORANG PRIBADI - I Wayan Budi Satriya; Rai Dwi Andayai W; Ni Putu Trisna Windika Pratiwi (JURNAL SEWAKA BHAKTI, 2023)
The use of an identification number (NIK) as a taxpayer identification number (NPWP) is one of the provisions stipulated in the tax harmonization law, which is related to administrative reform in the field of taxation. Given the importance of the process of matching NIK to NPWP not only for taxpayers but also for the government, as well as the consequences that will be received if individual taxpayers do not match, it is felt necessary to socialize as well as assistance for individual taxpayers to match NIK to NPWP. With this socialization and assistance, the public, especially individual taxpayers who come to the KPP Pratama Tabanan, will obtain information and avoid the difficulties and losses that will be incurred if, by the end of 2023, their NIK has not yet been matched to become an NPWP. The process of matching NIK to NPWP is carried out using the website www.djponline.pajak.go.id by following the stages according to those stipulated in the Minister of Finance Regulation number 112/PMK.03/2022 concerning taxpayer identification numbers for individual taxpayers, corporate taxpayers, and government agency taxpayers.